Sejarah Perkembangan dan Peradaban Islam di Afrika Utara - Putri Nadila; Nasril Nasril (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
The development of Islam in North Africa began during the reign of Caliph Umar bin Khattab (634–644 AD), who sent Amru bin Ash to conquer Egypt. This effort was then systematically continued by the ruling dynasties that followed. The spread of Islam by Muslim rulers not only made Arabic the official language spoken by Muslim communities in various regions, especially North Africa, but also had a great influence on civilization as a whole. History records various advances in North Africa, both in the fields of government administration, science, architecture, and historical buildings. The pattern of the relationship between the ruler and the community also shows how Islam is a blessing for all nature (rahmatan lil 'alamin). The splendor of buildings with high architecture is proof that only an advanced, stable, and prosperous government is able to achieve it.